Analisis Faktor Kesulitan Membaca Permulaan Siswa Kelas II MI Pejagatan Kebumen - Novita Tri Mulyani; Rose Kusumaningratri (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2026)
Early reading ability is a basic skill that determines students' success in understanding various learning materials. However, some lower grade students still experience difficulties in recognizing letters, pronouncing sounds, spelling, and reading fluently. This study aims to describe the forms of reading difficulties, the causal factors, and teachers' efforts to overcome reading difficulties in grade II students of MI Pejagatan Kutowinangun, Kebumen. The study used a descriptive method with a qualitative approach. The research informants consisted of grade II teachers, the principal, and a female student who experienced reading difficulties. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results showed that the reading difficulties experienced by students included a lack of ability to recognize and distinguish letters that look similar, letter substitution errors, difficulty pronouncing certain letters, dependence on the spelling process, and limited memory in combining spelling results into words. These difficulties are influenced by internal factors, such as interest, motivation, attention, memory ability, and mastery of letters, as well as external factors such as reading habits, family environment, opportunities to practice, reading materials, and parental guidance. Teachers address this through specialized guidance, attention and motivation, the use of appropriate methods and media, and collaboration with parents. Individual, gradual, and ongoing intervention is necessary to improve students' reading abilities.